Understanding the effect of high gas entrance velocity on Chinese hamster ovary (CHO) cell culture performance and its implications on bioreactor scale‐up and sparger design. Issue 6 (28th February 2020) - Chaudhary, Garima; Luo, Robin; George, Meena; Tescione, Lia; Khetan, Anurag; Lin, Henry
Abstract: There are three main potential sources for cell shear damage existing in stirred tank bioreactors. One is the potential high energy dissipation in the immediate impeller zones; another from small gas bubble burst; and third is from high gas entrance velocity (GEV) emitting from the sparger. While the first two have been thoroughly addressed for the scale‐up of Chinese hamster ovary (CHO) cell culture knowing that a wide tolerable agitation range with non‐damaging energy dissipation exists and the use of shear protectants like Pluronic F68 guard against cell damage caused by bubble burst, GEV remains a potential scale‐up problem across scales for the drilled hole or open pipe sparger designs. GEV as high as 170 m/s due to high gas flow rates and relatively small sparger hole diameters was observed to be significantly detrimental to cell culture performance in a 12, 000 L bioreactor when compared to a satellite 2 L bioreactor run with GEV of <1 m/s. Small scale study of GEV as high as 265 m/s confirmed this. Based on the results of this study, a critical GEV of >60 m/s for CHO cells is proposed, whereas previously 30 m/s has been reported for NS0 cells by Zhu, Cuenca, Zhou, and Varma (2008. Biotechnol. Bioeng., 101, 751–760). Implementation of new large scale spargers with larger diameter and more holes lowered GEV and helped improve the cell culture performance, closing the scale‐up gap. Design of such new spargers was even more critical when hole plugging was discovered during large scale cultivation hence exacerbating the GEV impact. Furthermore, development of a scale down model based on mimicry of the large scale GEV profile as a function of time was proven to be beneficial for reproducing large scale results. Abstract : Poor 12, 000 L bioreactor scale‐up performance is caused by high sparger gas entrance velocity (GEV). This high GEV impact is demonstrated by the high GEV 2 L model compared to the low GEV 2 L model.